Temuan Mikroplastik pada Sedimen Sungai Progo dan Sungai Opak Kabupaten Bantul - Utami, Inggit (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
In Bantul Regency, there are two large rivers that are used as raw water and fishing grounds for residents, namely the Opak River and the Progo River, where microplastic pollution has not been recorded. In fact, microplastics have been widely publicized as contaminating rivers in Indonesia and endangering living things if consumed.This study aims to compare the abundance of microplastics in the sediments of the Opak River and the Progo River in Bantul Regency. Sediment sampling was carried out in December 2020 where each river had two stations and three sediment samples were taken in one station. Each sample was filtered, dried, weighed dry, density separated, visually sorted to calculate the abundance of microplastics. The results found that microplastics were identified in all sediment samples from the Progo River and the Opak River.with the range of microplastic abundance in the Opak River was 314.54 to 3,729.67 particles/kg and in the Progo River it was 209.37 to 1,173.25 particles/kg. The highest abundance of microplastics was found in the sediment samples of the Opak River with an average of 1,799.33 ± 1,430.87 particles/kg. The confluence with the Code River, Gadjahwong River and Oyo River, as well as processed leachate of Piyungan Landfill discharge into the Opak River makes the abundance of microplastics in the river very high, especially in the downstream of the river. Keywords: abundance, bantul, microplastics, opak river, progo river